Chilling rather than photoperiod controls budburst for gymnosperm species in subtropical China. (12th July 2021) - Pan, Yuan-Qi; Zeng, Xiu; Chen, Wen-De; Tang, Xin-Ran; Dai, Kui; Du, Yan-Jun; Song, Xi-Qiang
Abstract: The mechanisms regulating spring phenology have been extensively studied in angiosperm species. However, given that gymnosperms and angiosperms diverged 300 million years ago, phenology may be triggered by different cues in gymnosperm species. The regulatory mechanisms of phenology in subtropical regions remain largely unknown. In combination, it remains untested whether subtropical gymnosperm species have chilling requirements and are photosensitive. We conducted a climate chamber experiment with three chilling and three photoperiod treatments to investigate budburst during an 8-week forcing period. We tested whether budburst of eight gymnosperms species ( Cryptomeria japonica, Cunninghamia lanceolata, Cupressus funebris, Ginkgo biloba, Metasequoia glyptostroboides, Pinus massoniana, Pseudolarix amabilis and Podocarpus macrophyllus ) was photoperiod sensitive or has strong chilling requirements and whether photoperiod or chilling was more important for advancing budburst. Chilling advanced budburst and increased the percentage of budburst for gymnosperm species. Gymnosperm species required moderate chilling days to advance budburst. Interestingly, the forcing requirement for gymnosperm species was higher than that for angiosperms in the same forest, suggesting that gymnosperms may need more cumulative forcing to initiate budburst than do angiosperms. Compared with temperate gymnosperm species in Germany (194–600 °C days), the subtropical species studied here had a much higher forcing requirement (814–1150 °C days). The effects of photoperiod were minor, suggesting that chilling outweighs photoperiod in advancing budburst of gymnosperm species in this subtropical region. These results reveal that increased winter temperatures with continued global warming may impact not only angiosperms but also gymnosperms, leading to their delayed spring budburst.